PENGARUH RASIO TEPUNG TAPIOKA DAN SERBUK DAUN PEPAYA (Carica papaya L.) PADA PEMBUATAN KUE SEMPRIT TERHADAP SIFAT FISIK DAN KIMIA - Rahel Silvia Mayasari; Laili Hidayati; Wiwik Wahyuni (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2023)
Papaya leaf are not one of the richest natural resources in Indonesia which is the utilization is not optimal. One way to optimize the utilization of papaya leaf is to process papaya leaf into powder. Papaya leaf powder will be applied to processed pastries that add variety to semprit cake. The purpose of making a semprit cake with a ratio of tapioca flour and papaya leaf powder is to variety of semprit cake in texture, color, water content and protein content. This research was an experimental study using a completely randomized design (CRD) research method with one factor (ratio of tapioca flour and papaya leaf powder). The factors used were 95%: 5%, 90%: 10%, 85%: 15%. The data from this research were statistically tested using One Way ANOVA and continued with the DMRT (Duncan’s Multiple Range Test) test if there was a significant difference. The results of statistical analysis showed significant differences in protein content, brightness level, yellowness level and texture.